2017
DOI: 10.1080/14786419.2017.1402324
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from Triclisia gilletii (De Wild) Staner (Menispermaceae) with antimycobacterial activity against Mycobacterium tuberculosis

Abstract: Triclisinone (2), a new ochnaflavone derivative, was isolated from the aerial parts of Triclisia gilletii, along with known drypemolundein B (1) and eight other known compounds. The chemical shifts of drypemolundein B (1) have been partially revised based on reinterpretation of NMR spectroscopic data. The eight other secondary metabolites are composed of: (+)-nonacosan-10-ol (3); stigmasterol (4), 3-O-β-D-glucopyranosylsitosterol (5), 3-O-β-D-glucopyranosylstigmasterol (6); oleanic acid (7); myricetin (8), que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In Ondo State, located in the South Western part of Nigeria, the plant which is usually called 'Peshe' in Ondo City or 'Ogbogan' in Okeluse, Ondo State, Nigeria, and Akan-Akyem Sanhoma in Ghana is used locally for the management of swelling of extremities and other kidney-related diseases or infections either singly or in combination with other condiments by traditional practitioners. Tiam et al [12] reported its usage for the management of edema and anemia which by our bet is closest to kidney function.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In Ondo State, located in the South Western part of Nigeria, the plant which is usually called 'Peshe' in Ondo City or 'Ogbogan' in Okeluse, Ondo State, Nigeria, and Akan-Akyem Sanhoma in Ghana is used locally for the management of swelling of extremities and other kidney-related diseases or infections either singly or in combination with other condiments by traditional practitioners. Tiam et al [12] reported its usage for the management of edema and anemia which by our bet is closest to kidney function.…”
Section: Introductionmentioning
confidence: 83%
“…Increased proteinuria, albuminuria, and glucosuria in this study indicate possible glomerular and tubular damage as a result of ethane-1,2-diol administration. The protectivity of TGME on the renal epithelial could be ascribed to the antioxidant power of quercetin and oleanolic acid present in the plant [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting points were uncorrected and were measured on a Mettler Toledo instrument. IR spectra were recorded on an Alpha FT-IR spectrometer from Bruker, while 1D and 2D NMR spectra were obtained on a Bruker DRX 500 (500 MHz for 1 H and 125 MHz for 13 Silica gel 60 (230-400 mesh E. Merck, Darmstadt, Germany) and Sephadex® LH-20 were employed for CC, the solvent mixing systems for elution were mainly CH2Cl2/MeOH for the phytochemical study with increasing polarity and pure MeOH, while precoated aluminum sheets silica gel 60 F254 were used for TLC [47].…”
Section: Generalmentioning
confidence: 99%